An Increased Number of Perineural Invasions Is Independently Associated With Poor Survival of Patients With Resectable Pancreatic Ductal Adenocarcinoma. Issue 8 (November 2015) - Kondo, Naru; Murakami, Yoshiaki; Uemura, Kenichiro; Hashimoto, Yasushi; Nakagawa, Naoya; Sasaki, Hayato; Sueda, Taijiro
Abstract : Objectives: The aim of this study was to investigate the impact of the number of perineural invasions (PNIs) in resected specimens on the survival of patients with pancreatic ductal adenocarcinoma (PDAC). Methods: A retrospective cohort study of 209 patients underwent surgical resection for PDAC between 1999 and 2013 was performed. The severity of PNI was evaluated by counting the number of PNIs in all sections with PDAC. The relationships of the number of PNIs with disease-free survival (DFS) and overall survival (OS) were analyzed. Results: At least 1 PNI was observed in 197 (94%) of 209 patients. Significant differences in DFS and OS were found between groups when analyzed by the median number of PNIs (≥25 vs <25) (DFS: P < 0.0001; OS: P < 0.0001) and among tertiles greater than 40 versus 40 to 14 versus less than 14 (DFS: P < 0.0001, OS: P < 0.0001). By multivariate analysis, an increased number of PNIs (>40 vs 40–14 vs <14) was identified as an independent risk factor for poor DFS ( P < 0.0001) and OS ( P < 0.0001). Conclusions: The severity of PNI evaluated by counting the number of PNIs in resected specimens was useful for predicting the prognosis of patients with resectable PDAC.